2009
DOI: 10.1111/j.1095-8649.2008.02134.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the growth rate of chub Leuciscus cephalus along a longitudinal river gradient

Abstract: An increase in individual growth rate of chub Leuciscus cephalus along a longitudinal river gradient of the Rhône River basin was observed and supported by significant differences between mean growth rates of successive river size groups. The potential implications of the results for studies on species traits variability along large-scale environmental gradients are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The juvenile growth of S. cephalus also significantly reduced with increasing latitude, with this consistent with Tedesco et al (2009) who suggested higher temperatures were coincident with faster chub growth rates in a study comparing 15 populations along a longitudinal river gradient. There was, however, no relationship between their back-calculated length at the last annulus and latitude, suggesting that latitude (and thus temperature) was a more important influence on their juvenile growth.…”
Section: Figuresupporting
confidence: 84%
“…The juvenile growth of S. cephalus also significantly reduced with increasing latitude, with this consistent with Tedesco et al (2009) who suggested higher temperatures were coincident with faster chub growth rates in a study comparing 15 populations along a longitudinal river gradient. There was, however, no relationship between their back-calculated length at the last annulus and latitude, suggesting that latitude (and thus temperature) was a more important influence on their juvenile growth.…”
Section: Figuresupporting
confidence: 84%
“…() suggesting that where species had expanding ranges, this was influenced more by changes in the seasonality of temperatures, whereas where ranges contract, it is due to the interaction of temperature change and alterations in precipitation patterns. Although it was unable to be tested further here, the range contraction of S. cephalus predicted under all climate change projections might relate to this interaction, given their natural distribution in more southern latitudes in Europe (Tedesco et al ., ), where air temperatures tend to be higher than for Great Britain. For G. gobio and L. leuciscus , predictions suggested some climate thresholds might exist, given their predicted expansions of climate space under low‐emission projections of climate space but constrictions under high emissions.…”
Section: Discussionmentioning
confidence: 95%
“…RDA-based variance-partitioning methods showed that environmental variables were in general more important than spatial ones in determining metacommunity structure. lakes, large rivers) (Tedesco, Sagnes & Laroche, 2009;Szaló ky, 2003;TE, pers. in time) in the relative role of spatial structuring (potentially dispersal limitation) and species sorting mechanisms may play in this metacommunity.…”
Section: Discussionmentioning
confidence: 99%